Curiosity Dan Thaharah Pada Pai (Eksperimen di SMP Negeri 218 ) Jakarta - Suhardin, Suhardin (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
The objective of this research to find out the effect of curiosity with student knowledge of thaharah. The research was conducted in SMP 218 Jakarta using 2X1 design involving 60 students chosen by using purposive random sampling. The data analysis and interpretation indicated that: There is significant difference in students knowledge of thaharah between high curiosity and low curiosity. The research conclution, curiosity have effecth with student knowledge of thaharah. Keywords: Curiosity, Thaharah, PAI.